Estudio geológico-estructural a escala 1:5,000 en el primer tramo del canal de riego campana-Malacatos ubicado en el sector El Porvenir, parroquia Malacatos, cantón y provincia Loja. - Quizhpe Piedra, Rommel Andres (2020)
The following thesis work “Geological-Structural Study at scale 1: 5,000 in the first section of the Campana-Malacatos Irrigation Canal located in the El Porvenir, Malacatos Parish and Loja Province”, includes the towns of Santa Gertrudis and El Porvenir; The study area reaches an area of 179 Ha, which runs along the first section of the irrigation canal with 4.6 km. The topographic map at 1: 5000 scale was made with the information provided by the Loja Provincial Council, in addition the information was supplemented with the slope and geomorphological map that allowed us to obtain the specific information of the study area that presents a relief with very steep slopes. The structural geological photointerpretation of the study area was carried out with the use of aerial photographs provided by the Ministry of Agriculture and Livestock through its SIGTIERRAS program at a scale of 1: 5,000, which allowed observing structural geological characteristics as inverse failures, two types were analyzed Drainage network dendritic network and subparallel network characteristics of metamorphic environments. The geological mapping was carried out by means of the detailed survey and description of each one of the natural and artificial outcrops, to this the information obtained in the photointerpretation was added and the structural geological map was obtained as a result of 1: 5000 scale, in the which can be seen a metamorphic domain of the Chigüinda Unit with intercalations of quartzite, phyllite and shale with the presence of colluvial and alluvial material. Keywords: Geological failure, foliation, metamorphism, raised terrace, recrystallization, micro-deployment, photointerpretation.